Simulation study for controlling direct current motor position utilising fuzzy logic controller - Nurainaa, Elias; Nafrizuan, Mat Yahya (Universiti Malaysia Pahang, 2018)
A fuzzy logic controller (FLC) modelled with MATLAB toolbox that is implemented for position control of a direct current (DC) motor is presented in this paper. The position control is an adaptation of an assisted lifting device system. Due to the existing assisted lifting device problems that lift the load slowly and having lack of accuracy, this research is conducted to improve current assisted lifting device with the introduction of a DC motor and a fuzzy logic controller (FLC) that can improve position accuracy, especially when loading the loads. The DC motor was modelled, converted to a subsystem in Simulink and then the MATLAB toolbox is used to design the FLC. The methodology covers the simulation and modelling of the DC motor, fuzzy logic controller and different transfer functions for DC motor model as a benchmark to the performance of the fuzzy system. The outcomes acquired from the scope of the simulation was analysed. Parameters such as the rise and settling time in seconds and maximum overshoot in percentage are observed to be compared with different types of transfer functions that are used for the dynamic response of the closed-loop system and system with and without a controller that was used as references. The overall performance shows that a system with FLC performs well compared to the system without FLC.